2018
DOI: 10.1136/bjsports-2016-097444
|View full text |Cite
|
Sign up to set email alerts
|

Are corticosteroid injections more beneficial than anaesthetic injections alone in the management of rotator cuff-related shoulder pain? A systematic review

Abstract: PROSPERO CRD42016033161.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 59 publications
0
28
0
1
Order By: Relevance
“…One large difference in methodology is that the majority of those enrolled in one-time single-site injections were compared to active interventions of enthesis saline, which has demonstrated some efficacy in the study of Bertrand et al, and subacromial corticosteroid injection, which has previously demonstrated efficacy in rotator cuff tendinopathy. 11,[24][25][26] Another methodologic difference is that patients included in one-time single-site injection studies tended to have milder baseline pain with lower pain intensity scores and improved baseline function with low SPADI scores and more active range of motion. Despite these methodologic differences, repeat multisite dextrose prolotherapy protocols demonstrated larger absolute improvements in VAS, SPADI, and range of motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One large difference in methodology is that the majority of those enrolled in one-time single-site injections were compared to active interventions of enthesis saline, which has demonstrated some efficacy in the study of Bertrand et al, and subacromial corticosteroid injection, which has previously demonstrated efficacy in rotator cuff tendinopathy. 11,[24][25][26] Another methodologic difference is that patients included in one-time single-site injection studies tended to have milder baseline pain with lower pain intensity scores and improved baseline function with low SPADI scores and more active range of motion. Despite these methodologic differences, repeat multisite dextrose prolotherapy protocols demonstrated larger absolute improvements in VAS, SPADI, and range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Although both groups improved similarly, previous studies of corticosteroid demonstrate a short-term benefit, however, significant disease recurrence by 1-year follow-up. 11,25,27,40 Due to the significant variation between the one-time single-site injection and repeat multisite injection protocols utilized, it is unknown whether patients receiving dextrose prolotherapy would continue to improve or maintain their improvements at 1 year as seen in Seven et al and Bertrand et al However, there is potential, based on the proposed mechanism of dextrose and results of repeat multisite injection protocols that patients may continue to improve or merely maintain their improvements at a 1-year follow-up, whereas patients with corticosteroid will have significant disease recurrence. 11,25,27,40 Recently there has been concern regarding subacromial corticosteroid injection for rotator cuff tendinopathies and its effects on tendon integrity, [41][42][43][44] longterm disease recurrence and progression, [41][42][43][44] and effect on future surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Injection therapy: Discussion may involve explaining that the potential benefit of an injection is likely to be a small and short-term reduction in pain. Either corticosteroid or local anaesthetic injections can be used, but the quality of the research evidence about their effect in people with rotator cuff related shoulder pain is low [36]. When corticosteroid injections are compared to a placebo, a small reduction in pain may occur between about 4 to 8 weeks after the injection, however, this benefit is usually not maintained by about 3 months [37].…”
Section: Key Issues To Explore In the Decision-making Processmentioning
confidence: 99%
“…In young patients with traumatic tear, there is no place for medical treatment: surgical repair (open or arthroscopic approach) should be quickly performed to avoid both tendon retraction and fatty infiltration that lead to lower clinical outcomes. In older patients with degenerative tear, the medical treatment must be first attempted with corticosteroid injections that are well known to be effective on pain [32]. Contraindications to repair are major glenohumeral arthropathy, fatty SSC muscle infiltration stage >2, active infection and significant medical comorbidities.…”
Section: Indications Of Arthroscopic Repairmentioning
confidence: 99%